FACULTY DEVELOPMENT PROGRAMS: THE FREQUENCY AND VARIETY OF PROFESSIONAL DEVELOPMENT PROGRAMS AVAILABLE TO ONLINE INSTRUCTORS - Jennifer Heather Herman (Online Learning, 2012)
Online education is no longer a peripheral phenomenon in higher education: over one-third of faculty have taught or developed an online course. As institutions of higher education expand their online education offerings, administrators need to recognize that supporting faculty through the use of incentives and through effective faculty development programs for online instruction is important to the improvement of the quality of educational programs. This quantitative study used an online survey to investigate the types and frequency of faculty development programs for online instruction at institutions with an established teaching and learning development unit (TLDU). The average TLDU offered about fifteen different types of faculty development programs, the most common being websites, technical services, printed materials, and consultation with instructional design experts.